Financial literacy promotes financial inclusion in both poor and rich countries - Antonia Grohmann; Lukas Menkhoff (DIW Economic Bulletin, 2017)
For social and economic reasons, national economies benefit from the inclusion of as many people as possible in financial services. In a cross country study, the present study shows that financial literacy for the general population promotes financial inclusion. This relationship goes beyond the effect of higher economic or financial development. And the effect of higher levels of financial literacy is greatest on the 'use of financial products' in financial systems that are more developed. On the contrary, the educational effect on 'access to finance' is greatest for countries that are financially less developed. Economic policy that targets financial inclusion should therefore not only concentrate on financial infrastructure, but also on improving financial literacy.
Keywords: G2; O1; D14; 330; financial inclusion; financial literacy; financial institutions